Healthcare Seeking Behaviour among Geriatric Women Residing in Urban Resettlement Colony of Delhi - Tulika Singh; Seetharamiah Nagesh (Medsci Publications, 2018)
Introduction: As the elderly population is increasing, diseases and disability in them are also at a rise. While a longer life may offer greater fulfilment in some ways, it also presents multifaceted health problems and increases the burden of providing health care services. It is necessary to understand health care seeking behavior with its determinants to sensitize the geriatric women towards their needs and priorities. Methodology: A community based cross sectional study for the duration of one year was conducted among 512 geriatric women (≥60 years) of a resettlement colony of Delhi. Structured interview was conducted to elicit information on health care seeking behavior of Geriatric women. Data was analyzed using SPSS 16. Results: Majority (80.7%) of the geriatric women were aware of the health facilities around and 48.1% preferred government facility. 55.9% of the participants had visited health facility once in the last one year. Reasons for not seeking health care were lack of money, drug prescribed not available, no felt need, distance too far, long waiting time and attitude of health workers. Conclusion: The study of health care seeking behavior of elderly women gains importance for formulating geriatric friendly health services in the community.